Novel diagnostic and analytical applications of benchtop time-domain NMR. - Robinson, Michelle Denise (East Carolina University, 2015)
High-resolution nuclear magnetic resonance (NMR) spectroscopy is a powerful technique, yet practical application outside of the research laboratory has been limited due to the high cost and complexity of the instrumentation. Recently, miniaturized low-field benchtop time-domain NMR (TD-NMR) instruments have been developed to solve practical problems within the industrial setting. While the low-field instruments sacrifice some degree of sensitivity and resolution, they are capable of powerful relaxation time analysis and have gained popularity due to their simplicity and cost effectiveness. Currently these instruments are utilized primarily in the food, agricultural and pharmaceutical industry. This project was initiated to investigate the utility of benchtop TD-NMR in clinical diagnostics and health assessment. Using TD-NMR relaxometry, we analyzed a variety of complex biological liquids, which included oil-phase lipids, purified proteins and lipoproteins, and whole human serum and plasma. For oil-phase non-esterified fatty acids, we demonstrated that the NMR T2 relaxation times were sensitive to hydrocarbon chain structure, particularly the number of cis-double bonds, which impact chain packing and fluidity. Triglyceride mixtures displayed the same sensitivity to double bond content and fluidity. Therefore, we developed a practical method for using benchtop-TD NMR to determine the omega-3 fatty acid content of nutritional supplements. Analysis of aqueous biological samples suffered initially from radiation damping and hardware artifacts. Therefore, we developed new methods to optimize TD-NMR analysis of water-rich samples such as human blood serum. The T2 profile of whole human serum or plasma displayed four resolved T2 peaks. One was the intense water peak, which correlated with biomarkers of insulin resistance, dyslipidemia, oxidative stress and inflammation. The other three peaks monitor the molecular motions of the lipid and protein components in serum and plasma. In an apparently healthy population of human subjects, the lipid-protein T2 values correlated with insulin resistance biomarkers by detecting metabolic changes in proteins and lipoproteins. The analysis of human serum and plasma using TD-NMR shows promise as a front-line health screening tool for identifying individuals at risk for developing diabetes, cardiovascular disease and Alzheimer's disease.
Keywords: Biochemistry; Biomedical engineering; Benchtop time-domain NMR; Fluidity; Lipoprotein; Metabolic syndrome; Omega-3; Relaxometry; Biological Markers--metabolism; Diagnosis--methods; Diagnostic Techniques and Procedures--methods; Magnetic Resonance Spectroscopy--methods; Magnetic Resonance Imaging--methods